Association between Exposure to Traffic-Related Air Pollution and Prevalence of Allergic Diseases in Children, Seoul, Korea. (13th September 2017) - Yi, Seon-Ju; Shon, Changwoo; Min, Kyung-Duk; Kim, Hwan-Cheol; Leem, Jong-Han; Kwon, Ho-Jang; Hong, Soyoung; Kim, KyooSang; Kim, Sun-Young
Abstract : Although there has been suggestive evidence of the association between TRAP and ADs, findings remained inconsistent possibly due to limited population. We investigated the association between TRAP and ADs in a large population of children with rich spatial coverage and expanded age span in Seoul, Korea. TRAP exposures were estimated by categorized proximity to the nearest major road (≤150, 150–300, 300–500, and >500 m) and density of major roads within 300 meters from children's residences. We estimated the association between two TRAP exposures and three ADs using generalized mixed model after adjusting for individual characteristics. We also investigated whether the association varied by household and regional socioeconomic status. We found associations of atopic eczema with road density [OR = 1.08; 95% CI = 1.01–1.15] and road proximity [1.15, 1.01–1.32; 1.17, 1.03–1.34; and 1.16, 1.01–1.34 for ≤150, 150–300, and 300–500 m, resp., compared to >500 m]. There was no association with asthma and allergic rhinitis. Effect estimates were generally the highest in the low socioeconomic region. Children living in areas surrounded by large and busy roads were likely to be at greater risks for atopic eczema, with increased vulnerability when living in deprived areas.